PROFIL BISNIS STARTUP VIRGIN COCONUT OIL MEMANFAATKAN BUSINESS MODEL CANVAS (BMC) - wulandary, Ayu; R, Fitriani; Hartina, Hartina (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
The business of the Bulowattang village women farmer group is a business that makes herbal oil or known as VCO. VCO is products that have many benefits in terms of health and beauty. Therefore, this business is able to compete with other products and is able to develop rapidly in the future. According to the results of this research, using the canvas business model, it has displayed comprehensive business activities, visible from each business model elements that have described all business activities in the vco business of the Bulowattang Village women's group that will be implemented.